Strategy for Reducing Stunting Rate Using Analytical Hierarchy Process in Garut District - Karmila, Mila; Kania, Ikeu; Fadhlurrohman, Mochammad Iqbal; Ananda Hilmaniah, Dena (Jurnal Studi Pemerintahan, 2024)
This investigation seeks to select the most effective strategy for reducing the stunting rate in the Garut district so that the high stunting rate can be de- creased. This study used qualitative methods to collect primary and secondary data through direct observation and interviews. Additionally, supplementary data was obtained from literature reviews, interview guidelines, recording equipment, and cameras used as research instruments. The analysis method uses the Analytical Hierarchy Process method along with an analysis tool called Expert Choice software to make choosing the most important criteria, sub-criteria, and options easier. Therefore, in this research, the selected sub-criteria and alternatives are sub-criteria for RT drinking water management and alternative socialization that must be prioritized to reduce the garut stunting rate. In contrast to the RT Drinking Water Management Subcriteria, which has a weight of 550 and a consistency value of 0.0014 and is deemed consistent because the consistency value is less than 0.1, the Alternative Socialization Subcriteria has a weight of 361 and a consistency value of 0.02 and is also deemed consistent because the consistency value is less than 0.1. Then, the priority results from the analytical hierarchy process were strengthened using a SWOT analysis, with the RT Drinking Water Management and Alternative Socialization sub-criteria having good weight and being located in quadrant I, which has the capability and potential to reduce the stunting rate of the Garut Regency’s.